Polar Desolvation and Position 226 of Pancreatic and Neutrophil Elastases Are Crucial to their Affinity for the Kunitz-Type Inhibitors ShPI-1 and ShPI-1/K13L - Hernández González, Jorge Enrique (PLoS One, 2015)
The Kunitz-type protease inhibitor ShPI-1 inhibits human neutrophil elastase (HNE, K (i) = 2.35·10(−8) M) but does not interact with the porcine pancreatic elastase (PPE); whereas its P1 site variant, ShPI-1/K13L, inhibits both HNE and PPE (K (i) = 1.3·10(−9) M, and K (i) = 1.2·10(−8) M, respectively). By employing a combination of molecular modeling tools, e.g., structural alignment, molecular dynamics simulations and Molecular Mechanics Generalized-Born/Poisson-Boltzmann Surface Area free energy calculations, we showed that D226 of HNE plays a critical role in the interaction of this enzyme with ShPI-1 through the formation of a strong salt bridge and hydrogen bonds with K13 at the inhibitor’s P1 site, which compensate the unfavorable polar-desolvation penalty of the latter residue. Conversely, T226 of PPE is unable to establish strong interactions with K13, thereby precluding the insertion of K13 side-chain into the S1 subsite of this enzyme. An alternative conformation of K13 site-chain placed at the entrance of the S1 subsite of PPE, similar to that observed in the crystal structure of ShPI-1 in complex with chymotrypsin (PDB: 3T62), is also unfavorable due to the lack of stabilizing pair-wise interactions. In addition, our results suggest that the higher affinity of ShPI-1/K13L for both elastases mainly arises from the lower polar-desolvation penalty of L13 compared to that of K13, and not from stronger pair-wise interactions of the former residue with those of each enzyme. These results provide insights into the PPE and HNE inhibition and may contribute to the design of more potent and/or specific inhibitors toward one of these proteases.